Exploring the Measurement of Productivity in Agile Teams in the University Context: Acceptance and Comprehensive Qualitative Assessment - Guerrero, Marcela; Hernandez, Giovanni (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2026)
Productivity measurement in agile software development (ASD) teams is an important topic in industry because it provides essential information for decision-making and helps adjust team behavior to support continuous improvement. However, developing the necessary competencies in undergraduate students to incorporate this process through a Software Engineering course has become a challenge due to the high level of abstraction involved. This article presents the main findings from the adoption of a productivity measurement process implemented with 110 students from Higher Education Institutions in Colombia. Organized into agile teams, the students developed a software product. The results show a high level of acceptance of the proposed measurement process. The main difficulties encountered were related to the practical implementation of metrics. Regarding areas for improvement, the use of a computational tool to support the proposed process is suggested in order to reduce its level of complexity.